Cognitive and Emotional Effects of Bilingualism Childhood and Adulthood - Umi Farisiyah (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2018)
Mastering more than one languages gives some advantages because of the correlation of the language and the brain. If we use more than one languages mean our brain has to work more that it works in one language. It means our brain has to be more active that can activate all the neurons of the brain and automatically make the brain much better in its functions. And of course, using more than one languages change how we assume and interpret everything in our surrounding. Using evidences from reaction time, eye-tracking, functional magnetic resonance imaging, and event-related potential research, it shows how language experience transforms cognitive control and emotion, two features that they are central to human communication. We suggest that managing multiple languages not only impacts cognitive control and emotion independently, but also the way in which they interact with each other. Within cognitive control, we present research suggesting that bilinguals demonstrate benefits compared to monolinguals and discuss the potential sources of these benefits, including parallel language activation and language switching. We also explore the potential links between linguistic and non-linguistic cognitive processes. Within emotion, we discuss whether bilinguals process emotions similarly across their first and second languages and consider how linguistic context and one’s cultural affiliation may impact memory (e.g., storage and retrieval) of emotional events. The evidence discussed in this chapter highlights the transformative effect that bilingual experience has on how human beings understand and interpret the world